'Out of the Box' leadership: action research towards school improvement. Issue 2 (15th March 2018) - Karagiorgi, Yiasemina; Afantiti-Lamprianou, Thekla; Alexandrou-Leonidou, Vassiliki; Karamanou, Marianna; Symeou, Loizos
Abstract: The contribution of Action Research (AR) to school improvement is well-documented. This study records the accounts of two primary school leaders, involved in AR projects that focused on the development of students' oral communication skills. Drawing data from diaries with fieldnotes and systematic reflections, the study presents leaders' experiences, as they translated feedback into modifications and redefinitions to bring about change. Despite difficulties encountered, the leaders acknowledged the value of collaborative school-based enquiry for teachers, students and themselves, mainly reflecting notions of catalytic and democratic validity. The paper highlights that AR as a tool for individual and school improvement, can enhance understandings of school performance and empower participants to focus on school outcomes in an educational context that does not implement accountability measures. AR can certainly help principals in Cyprus reconceptualise and rediscover their pedagogical role as instructional leaders to improve teaching and learning. Yet, to address outcome and process validity, the paper argues about the need for evaluative tools.